Encapsulating peritoneal sclerosis presenting with haemorrhagic ascites after transfer from peritoneal dialysis to haemodialysis - Chothia, MY; Davids, MR (African Journal of Nephrology, 2015)
<span style="color: #000000; font-family: ’Merrieweather sans’, sans-serif; font-size: 12.6px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: left; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #ffffff; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">A patient with end-stage kidney disease due to chronic glomerulonephritis was initiated on continuous ambulatoryperitoneal dialysis. After three years he was transferred to haemodialysis following recurrent episodes of peritonitis.After the commencement of haemodialysis the patient developed progressive abdominal distension; paracentesisrevealed bloody ascites. Radiographic imaging revealed features of small bowel obstruction with bowel loops matted tothe posterior abdominal wall. A diagnosis of encapsulating peritoneal sclerosis was made. Treatment with prednisonewas initiated but the patients condition steadily worsened and he demised a year later due to severe malnutrition andsepsis.